Modern Approaches To The Development Of Social Activity In Student Women - Tursunova Dilnavoz Tulqin kizi (Zien Journals, 2023)
The article analyzes the need to increase the social protection and intellectual activity of students, especially female students, in ensuring the development of society, and in this process the innovative factors of effective use of the opportunities of the subjects of the education system
Keywords: Society; development; students; women